Gut-Amygdala Interactions in Autism Spectrum Disorders: Developmental Roles via regulating Mitochondria, Exosomes, Immunity and microRNAs - Seo, Moonsang; Anderson, George (Current Pharmaceutical Design, 2019)
Background: Autism Spectrum Disorders (ASD) have long been conceived as developmental disorder. A growing body of data highlights a role for alterations in the gut in the pathoetiology and/or pathophysiology of ASD. Recent work shows alterations in the gut microbiome to have a significant impact on amygdala development in infancy, suggesting that the alterations in the gut microbiome may act to modulate not only amygdala development but how the amygdala modulates the development of the frontal cortex and other brain regions. Methods: This article reviews wide bodies of data pertaining to the developmental roles of the maternal and foetal gut and immune systems in the regulation of offspring brain development. Results: A number of processes seem to be important in mediating how genetic, epigenetic and environmental factors interact in early development to regulate such gut-mediated changes in the amygdala, wider brain functioning and inter-area connectivity, including via regulation of microRNA (miR)-451, 14-3-3 proteins, cytochrome P450 (CYP)1B1 and the melatonergic pathways. As well as a decrease in the activity of monoamine oxidase, heightened levels of in miR-451 and CYP1B1, coupled to decreased 14-3-3 act to inhibit the synthesis of N-acetylserotonin and melatonin, contributing to the hyperserotonemia that is often evident in ASD, with consequences for mitochondria functioning and the content of released exosomes. These same factors are likely to play a role in regulating placental changes that underpin the association of ASD with preeclampsia and other perinatal risk factors, including exposure to heavy metals and air pollutants. Such alterations in placental and gut processes act to change the amygdala-driven biological underpinnings of affect-cognitive and affect-sensory interactions in the brain. Conclusion: Such a perspective readily incorporates previously disparate bodies of data in ASD, including the role of the mu-opioid receptor, dopamine signaling and dopamine receptors, as well as the changes occurring to oxytocin and taurine levels. This has a number of treatment implications, the most readily applicable being the utilization of sodium butyrate and melatonin.
Keywords: mitochondria